2016
DOI: 10.1111/mcn.12262
|View full text |Cite
|
Sign up to set email alerts
|

Impact of small‐quantity lipid‐based nutrient supplement on hemoglobin, iron status and biomarkers of inflammation in pregnant Ghanaian women

Abstract: We examined hemoglobin (Hb, g/L), iron status (zinc protoporphyrin, ZPP, µmol/mol heme, and transferrin receptor, TfR, mg/L) and inflammation (C-reactive protein, CRP and alpha-1 glycoprotein, AGP) in pregnant Ghanaian women who participated in a randomized controlled trial. Women (n = 1320) received either 60 mg Fe + 400-µg folic acid (IFA); 18 micronutrients including 20-mg Fe (MMN) or small-quantity lipid-based nutrient supplements (SQ-LNS, 118 kcal/d) with the same micronutrient levels as in MMN, plus four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…These results are similar to those of the sister iLiNS‐DYAD trial in Ghana that had the same study design and interventions as the study in Malawi (Adu‐Afarwuah et al, ). In both sites, Hb and iron status were higher among those provided with IFA, compared with LNS and MMN.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results are similar to those of the sister iLiNS‐DYAD trial in Ghana that had the same study design and interventions as the study in Malawi (Adu‐Afarwuah et al, ). In both sites, Hb and iron status were higher among those provided with IFA, compared with LNS and MMN.…”
Section: Discussionsupporting
confidence: 82%
“…The primary aim of the iLiNS Project was to examine the effect of SQ‐LNS on birth outcomes and infant growth. Additionally, we have examined a wide range of secondary outcomes among pregnant women and infants, including haemoglobin (Hb) and iron status among pregnant Ghanaian women (Adu‐Afarwuah et al, ). In the present study, we examine the effect of three iron‐containing supplements (iron and folic acid [IFA], multiple micronutrient [MMN] capsule, and SQ‐LNS) on Hb and markers of iron status (zinc protoporphyrin [ZPP] and soluble transferrin receptor [sTfR]) among pregnant Malawian women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study population, the prevalence of ID anemia at enrollment was relatively low [w6%, with the use of a cutoff for anemia of hemoglobin concentration at ,100 g/L as is recommended for African populations (44,45)]. Women who received 60 mg Fe [iron-folic acid capsule (IFA)] from #20 wk of gestation until delivery had a lower prevalence of ID and anemia at 36 wk of gestation than women who received 20 mg Fe in either a lipid-based nutrient supplement (LNS) or a multiple-micronutrient capsule (46), but birth size was significantly greater in the LNS group compared with the IFA group especially among primiparous women (6). It is not possible to disentangle the effects of a lower compared with a higher dose of iron from those of the additional micronutrients provided via the LNS or multiple-micronutrient capsule, but the results illustrate that reducing maternal anemia and ID in the IFA group did not translate into greater birth size or a longer duration of gestation.…”
Section: Potential Effects Of Iron Supplementation On Birth Outcomes mentioning
confidence: 99%
“…The Breastfeeding, Antiretrovirals, and Nutrition Study in Malawi likewise found that postnatal lipid‐nutrient supplement prevented iron depletion in women using antiretrovirals (Widen et al, ). In the iLiNS‐DYAD study in Ghana, low‐calorie lipid‐nutrient supplements reduced maternal anemia, increased hemoglobin, and decreased iron deficiency (Adu‐Afarwuah et al, ), and younger women finished pregnancy with lower cortisol levels if they consumed lipid‐nutrient supplements relative to multiple micronutrients (Oaks et al, ). The same supplements administered in the iLiNS‐DYAD‐M study in Malawi did not differ in their effects on women's malaria immunity or risk, cortisol levels, or likelihood of being diagnosed with a reproductive tract infection (Chandrasiri et al, ; Nkhoma et al, ; Stewart et al, ).…”
Section: Prenatal Supplementation Studies: Contingent Outcomesmentioning
confidence: 99%